Kinship, Islam, and the politics of marriage in Jordan : affection and mercy - Hughes, Geoffrey F. (Public cultures of the Middle East and North Africa., 2021)
"In Kinship, Islam, and the Politics of Marriage in Jordan, Geoffrey Hughes sets out to trace the "marriage crisis" in Jordan and the Middle East. Rapid institutional, technological, and intellectual shifts in Jordan have challenged the traditional notions of marriage and the role of powerful patrilineal kin groups in society by promoting an alternative ideal of romantic love between husband and wife. Drawing on many years of fieldwork in rural Jordan, Kinship, Islam, and the Politics of Marriage in Jordan provides a firsthand look at how expectations around marriage are changing for young people in the Middle East even as they are still expected to raise money for housing, bridewealth, and a wedding. Kinship, Islam, and the Politics of Marriage in Jordan offers an intriguing look at the contrasts between the traditional values and social practices of rural Jordanians around marriage and the challenges and expectations of young people as their families negotiate the concept of kinship as part of the future of politics, family dynamics, and religious devotion"--